Influence of macro-and microclimatic conditions on thermal comfort of dairy cows - Tosetto, Martieli Regina (2014)
The goal was to assess the influence of thermal environment on thermal comfort of 15 multiparous lactating Holstein cows. Thermal comfort of the cows in the barn was assessed from the changes in their rectal temperature and respiratory frequency Air temperature and relative humidity were measured outside and inside the barn to characterize the macro-and microclimate. There was no correlation between micro and macroclimate considering the physiological parameters. The thermal environment variables and physiological parameters were within ideal limits according literature. Therefore, we concluded that the facility may have been effective considering the thermal comfort needs of dairy cows.